A Novel Cross-Pile Calibration Approach for Deriving Local Skin Friction Correlations of Bored Piles - Iskandar, Ali; Irawan, Agustinus Purna; Kawanda, Aksan (Engineering, Technology & Applied Science Research, 2026)
The design of bored piles in Jakarta is often conservative due to reliance on general empirical methods that fail to capture the high shaft friction characteristic of prevalent cemented soils in the area. This study introduces a Cross-Pile Calibration (CPC) strategy that develops site-specific correlations between Standard Penetration Test (SPT) N-values and maximum skin friction. This method uses a combination of load test data from multiple projects and fully mobilized piles to calibrate predictions for those with partial mobilization data in similar soil strata. The study proposes new linear correlations for key soil groups, including skin friction equal to 3.33 times the N-value for cemented sand, capped at 300 kPa, and skin friction equal to 4.0 times the N-value for clay-silt, capped at 160 kPa. Validation against 27 independent piles shows that, on average, applying the CPC-derived correlations within a rational framework yields shaft capacity projections that are 29% higher than those predicted by the classical Reese and Wright method, quantifying a significant reduction in design conservatism. This work provides a practical, data-driven framework for optimizing bored pile design in Jakarta’s complex geology.